BANDEIRA DE AÇO: música, identidade e cultura popular no Maranhão - OLIVEIRA JÚNIOR, José Alberto Campos de (2014)
In Maranhão, since the 80 s, it was created by the mass media communication the nomenclature "maranhense popular music" to define the musical production of composers and interpreters maranhenses after the release of the LP Bandeira de Aço (Flag Steel), recorded by Papete in 1978 and released by label Discos Marcus Pereira. The album served as a reference to arise a integrated arts movement based on the authenticity of the maranhense way of life , condensing the aesthetic , artistic, political and cultural effort, from regional musicality, but inserted in the proposal to be a poetical expression Brazilian music. Based on theoretical like Pierre Bourdieu, Renato Ortiz, Raymond Williams, this research intend to understand how Bandeira de Aço (Flag Steel) served as a symbol of regional cultural identity integrated to the idea of nation, following the flow and movement around the structure of Brazilian popular music (MPB), between the national- popular and industrialization of the disk market. The first chapter discusses the transition of representations of cultural identity in Maranhão, before linked to tradition and literary canons, until achieve to the appropriations of popular culture. The second chapter discusses how popular music was used in the social construction of the idea of the Brazilian nation, through the market of symbolic goods and cultural products with the advent of mass media to the consolidation of the phonographic industry market in the 70's. The third chapter analyzes the album Bandeira de Aço (Flag Steel) hard, trying to understand the relationship of appropriation of artistic material (songs) into a commercial product (the disk) and how it served to structure the symbolic field called "maranhense popular music."